Human milk oligosaccharides (HMOS) for infant health and microbiome development - Regina Karim (World Nutrition Journal, 2023)
HMO stands HUMAN MILK OLIGOSACCHARIDES, which act as a prebiotic found naturally in breastmilk. They are the third largest solid component in breast milk after lactose and fat.